2021
DOI: 10.1016/j.ultsonch.2021.105739
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-homogenization-assisted extraction of polyphenols from coconut mesocarp: Optimization study

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 33 publications
1
19
0
Order By: Relevance
“…Compared with traditional extraction methods, ultrasound-assisted extraction (UAE) can utilize the mechanical, cavitation and thermal effects of ultrasonic waves to overcome the weaknesses of traditional extraction and significantly improve the extraction efficiency with lower consumption [ 13 , 14 , 15 ]. Exactly, the propagation of ultrasonic mechanical thermal vibration contributes to the dissolution and diffusion of plant active ingredients [ 16 ]. The cavitation releases energy and generates instantaneous pressure and high temperature to cause the cell wall to be cracked, which prompts the contents that are directly dissolved and fully contacted with the solvent [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with traditional extraction methods, ultrasound-assisted extraction (UAE) can utilize the mechanical, cavitation and thermal effects of ultrasonic waves to overcome the weaknesses of traditional extraction and significantly improve the extraction efficiency with lower consumption [ 13 , 14 , 15 ]. Exactly, the propagation of ultrasonic mechanical thermal vibration contributes to the dissolution and diffusion of plant active ingredients [ 16 ]. The cavitation releases energy and generates instantaneous pressure and high temperature to cause the cell wall to be cracked, which prompts the contents that are directly dissolved and fully contacted with the solvent [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combined extraction (HUAEo and UHAEo) has synergistic effect, which is more conducive to the extraction of active ingredients. Our previous study on the extraction of polyphenols from coconut mesocarp also showed that the combined extraction improved the yield of total phenols and total flavonoids, especially UHAEo (Yang et al, 2021).…”
Section: The Hae and Combined Extractionmentioning
confidence: 81%
“…Coincidentally, the PPO activity and TFC of coconut mesocarp The combined extraction (HUAEo and UHAEo) is more conducive to the release of phenolic compounds in peony by-product. gradually increased in HUAE and UHAE during 10 min, however, the TPC reached the maximum at 5 min (Yang et al, 2021). In addition, the PR-TFC was significantly higher than PL-TFC, while the PR-TPC was the opposite.…”
Section: The Hae and Combined Extractionmentioning
confidence: 87%
See 1 more Smart Citation
“…The turbulent collapse of cavitation bubbles on the surface of the product creates micro jetting, generating surface peeling, erosion, and particle breakdown [ 77 ]. This further increases the area exposed to the ultrasonic field and facilitates the release of the compound inside the raw material into the solvent [ 78 ]. Since the mechanism of bubble formation and collapse is localised and short-lived, very little quantity of heat is transferred from the cavitational bubbles to the medium, causing only a gradual temperature increase in the medium.…”
Section: Applications Of Ultrasonic Waves In Food Processingmentioning
confidence: 99%